Bioethanol Production From Turkish Hazelnut Husk Process Design and Economic Evaluation - SAYAR, AHMET ALP; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU; PİNAR, ORKUN (SPRINGER, 2019)
The main objective of the current study is to develop and assess the preliminary synthetic design steps of an innovative and unprecedented bioprocess plant converting Turkish hazelnut husk into lignocellulosic ethanol with an emphasis on economic evaluation. Valorization of this agricultural waste would provide a promising economic potential and long-term sustainability with acceptable environmental impact. Preliminary economic evaluations are performed on several scenarios where the effects of changing various process design and operational inputs such as designed plant capacity, evaporation unit operation efficiency, and biocatalyst and nitrogen source prices are simulated. The total capital investment for the base case scenario with an annual throughput of 180,000 metric tons (MT) hazelnut husk is just above USD 111million. The annual operational costs for this case amount to USD 61million. Assuming a sales price of USD 1.50 per kg of bioethanol (achieved via governmental subsidy and tax incentives) the return on investment of the project comes to 12.61% with a 8year payback period. An uncertainty analysis performed on the annual hazelnut husk availability and biocatalyst and nitrogen source price fluctuations establishes a basis for further design of the process taking into account the risk factors associated with the project. The case studies and the uncertainty analysis confirm the fact that production of second generation bioethanol from hazelnut husk in Turkey is a worthwhile endeavor with an economic potential especially with additional social and environmental advantages.
Keywords: Bioethanol; Process design; Economic evaluation; Uncertainty analysis; Hazelnut husk; Process simulation; PROCESS SIMULATION; SACCHAROMYCES-CEREVISIAE; ENERGY-CONSUMPTION; CORN STOVER; OPTIMIZATION; ETHANOL; PRETREATMENT; HYDROLYSIS; PYROLYSIS; KINETICS